2016
DOI: 10.9755/ejfa.2015-05-296
|View full text |Cite
|
Sign up to set email alerts
|

Importance of camel milk for human health

Abstract: Camel milk against gastrointestinal disorders Camel milk contains a high concentration of antiinflammatory proteins, which have a positive health effect on the stomach and intestinal disorders. The high proportion of mono and polyunsaturated fatty acids and vitamin-rich composition provide improved carbohydrate metabolism (Karray et al., 2005; Konuspayeva et al., 2008). Moreover, it was found that fermented camel milk has an enzyme (Angiotensin I-converting enzyme, ACE) (Quan et al., 2008), which facilitates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 33 publications
5
67
0
Order By: Relevance
“…This supports the view that Th2 immunity in patients with chronic hepatitis C cannot regulate viral clearance (65). In keeping with previous findings concerning the use of camel milk to improve tuberculosis, problems with the spleen, dropsy, asthma, anemia, piles and jaundice (31), other lung ailments and treatment of diabetic patients (66), the present study demonstrated that, following treatment with camel milk, all generalized symptoms (including malaise, anorexia, fever, athralgia, indigestion and changes in the secondary sex characteristics) were resolved in all HCV patients in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This supports the view that Th2 immunity in patients with chronic hepatitis C cannot regulate viral clearance (65). In keeping with previous findings concerning the use of camel milk to improve tuberculosis, problems with the spleen, dropsy, asthma, anemia, piles and jaundice (31), other lung ailments and treatment of diabetic patients (66), the present study demonstrated that, following treatment with camel milk, all generalized symptoms (including malaise, anorexia, fever, athralgia, indigestion and changes in the secondary sex characteristics) were resolved in all HCV patients in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Lactoferrin (alone or in combination with other milk proteins) exhibits antibacterial, antiviral, antifungal, antiparasitic, immunomodulatory, anti-inflammatory and even antineoplastic effects (2529). It has been demonstrated that camel milk has therapeutic effects on cancer, jaundice, hepatitis B and C, diabetes, dropsy, tuberculosis, spleen problems, anemia, piles, food allergies, high cholesterol in the blood and asthma (30,31). …”
Section: Introductionmentioning
confidence: 99%
“…Despite the uniqueness of camel milk in terms of nutritional and therapeutic properties (Al haj and Al Kanhal 2010;Kaskous 2016;Khan and Alzohairy 2011), it does not form a desirable curd by lactic acid fermentation process. The fermented camel milk products have a watery consistency and have a fragile and poor structure (Abdel Rahman et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Camel milk and its ingredients have been claimed to have significant in vitro and in vivo activity against cancer, jaundice, hepatitis B and C, diabetes, dropsy, tuberculosis, spleen problems, anemia, piles, food allergies, high cholesterol in the blood and asthma (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). One of these unique ingredients is the camel heavy-chain antibodies which have advantages because of their low molecular weight, while their light chains are absent; they should bind their antigen by one single domain, the variable domain of the heavy chain, which is referred to as "VHH", a nanobody of only about 12 to 15 kDa molecular weight allowing its access to small spaces not accessible for conventional antibodies [42,43].…”
Section: Discussionmentioning
confidence: 99%